Serum microRNAs and chronic periodontitis: A case-control study. (May 2019) - Yoneda, Toshiki; Tomofuji, Takaaki; Ekuni, Daisuke; Azuma, Tetsuji; Maruyama, Takayuki; Fujimori, Kohei; Sugiura, Yoshio; Morita, Manabu
Highlights: MiRNAs exist in several body fluids, including serum. The relationship between serum miRNA profiles and chronic periodontitis is unclear. Microarray and RT-PCR were used to evaluate serum miRNA profiles and periodontitis. miRNAs could be serum biomarkers for chronic periodontitis. Abstract: Objective: An association is present between periodontitis and rates of expression of certain microRNAs (miRNAs) in periodontal tissue. However, the association between periodontitis and miRNA levels in human serum is unknown. We performed a case-control study in patients with chronic periodontitis to investigate serum miRNA levels. Design: We enrolled 30 healthy patients without periodontitis and 30 patients with chronic periodontitis. Participants underwent clinical examination, case selection, and a blood draw from the antecubital vein. Serum miRNA profiles were compared in samples from participants with and without chronic periodontitis using microarray and real-time PCR. Results: Microarray demonstrated seven miRNAs that were expressed <1/1.5 or >1.5 in the control group compared to the periodontitis group (p < 0.05). Real-time PCR showed that hsa-miR-664a-3p, hsa-miR-501-5p, and hsa-miR-21-3p were higher in the periodontitis group than the control group (p < 0.05). Conclusion: Hsa-miR-664a-3p, hsa-miR-501-5p, and hsa-miR-21-3p are candidate serum biomarkers for chronic periodontitis.